Makna Leksikal dan Kultural Geret Sapu di Desa Jambuwok Mojokerto dan Relevansi dalam Pembelajaran Bahasa Indonesia di Tingkat SMA - M. Nur Kholis; Iktarna Faris Sauqillah; Taswirul Afkar (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to explore in depth the implementation of the Geret Sapu tradition in Jambuwok Village, including an analysis of its lexical and cultural meanings, as well as its relevance to the teaching of Indonesian Language and Literature at the senior high school level. The research focuses on the traditional practices of the Jambuwok Village community, located in Mojokerto Regency, using a qualitative descriptive approach. Data were collected through documentation and interview techniques, with local residents serving as the research subjects. Data validity was ensured through source and method triangulation. Data analysis was carried out in three stages: data reduction, data display, and conclusion drawing. The findings reveal that the Geret Sapu tradition consists of two main stages: preparation and implementation. The ritual involves six symbolic objects, namely: a broomstick, water jug (kendi), mat, pillow, bolster, and soil. Semantic analysis was conducted through the interpretation of lexical and cultural meanings. These findings indicate that the cultural values embedded in the Geret Sapu tradition can be integrated into Indonesian Language and Literature learning as contextual material grounded in local culture.